2016
DOI: 10.1016/j.ins.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Network structure and resilience of Mafia syndicates

Abstract: In this paper we present the results of the study of Sicilian Mafia organization by using Social Network Analysis. The study investigates the network structure of a Mafia organization, describing its evolution and highlighting its plasticity to interventions targeting membership and its resilience to disruption caused by police operations. We analyze two different datasets about Mafia gangs built by examining different digital trails and judicial documents spanning a period of ten years: the former dataset inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 37 publications
(72 reference statements)
2
57
0
1
Order By: Relevance
“…Under such term, terrorist networks, fake-news spreading networks, malnets or botnets used in DDoS attacks, or for spreading worms and viruses, dark networks involved in various criminal activities like illegal arm selling or child pornography, and so forth can be understood [14][15][16][17][18][19][20]. Attack strategies on such harmful complex networks (i.e., node deletion and occasionally also edge deletion) are studied in [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Under such term, terrorist networks, fake-news spreading networks, malnets or botnets used in DDoS attacks, or for spreading worms and viruses, dark networks involved in various criminal activities like illegal arm selling or child pornography, and so forth can be understood [14][15][16][17][18][19][20]. Attack strategies on such harmful complex networks (i.e., node deletion and occasionally also edge deletion) are studied in [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Calderoni also found that actors in more central positions in the network were not necessarily associated with high-status members. These findings were supported by Agreste, Catanese, De Meo, Ferrara and Fiumara's (2016) study into the Sicilian Mafia in Italy. They found that "criminals high up in the organization hierarchy do not occupy the most central positions in the criminal network, and oftentimes do not appear in the reconstructed criminal network at all" (Agreste et al, 2016, p. 30), thus suggesting that centrality in a network does not mean that you need to hold a powerful position.…”
Section: Centralitysupporting
confidence: 66%
“…Previous research has explored the operations within a number of different criminal networks, for example drug trafficking networks (Morselli, 2001(Morselli, , 2003, terrorist networks (Krebs, 2001), transnational illegal networks (Bruinsma & Bernasco, 2004), Mafia networks (Agreste et al, 2016;Cayli, 2010;Paoli, 2003), organised crime networks (Le & Lauchs, 2013;Levi, 2008) and police corruption networks Lauchs, Keast, & Le, 2011;Lauchs, Keast, & Yousefpour, 2011). Research into these networks has found that each of these networks displays unique characteristics that enable them to operate covertly.…”
Section: Chapter Eight How Do Police Corruption Network Operate? Intmentioning
confidence: 99%
See 2 more Smart Citations